Big data now : current perspectives from O'Reilly radar. (O'Reilly Media, 2011)
This collection represents the full spectrum of data-related content we've published on O'Reilly Radar over the last year. Mike Loukides kicked things off in June 2010 with "What is data science?" and from there we've pursued the various threads and themes that naturally emerged. Now, roughly a year later, we can look back over all we've covered and identify a number of core data areas: Data issues -- The opportunities and ambiguities of the data space are evident in discussions around privacy, the implications of data-centric industries, and the debate about the phrase "data science" itsel.